Minat Siswa Kelas X Terhadap Pembelajaran Seni Budaya di SMA N 1 Bengkulu Selatan - Tri Intan Julita Kencana; Yensharti Yensharti (SENDRATASIK UNP, 2023)
The purpose of this study was to determine the interest of class X students in learning art and culture at SMA N 1 Bengkulu Selatan. This type of research is quantitative research and is described by descriptive statistics. The population in this study were students of class X SMA N 1 Bengkulu Selatan and the sample of the population studied was class X IPS 3. The instrument of this research was a questionnaire (questionnaire). Data collection techniques were carried out by distributing questionnaires, processing and returning the questionnaires. The data analysis technique was carried out using the Likert scale percentage formula. Students' feeling of pleasure towards learning art and culture at SMA N 1 Bengkulu Selatan is in the Medium category with a percentage of 60%, student involvement is in the medium category with a percentage of 60%. The students' interest is in the medium category with a percentage of 59% and the students' attention is in the medium category with a percentage of 58%. Thus, the overall interest of students in class X IPS 3 towards learning art and culture at SMA N 1 Bengkulu Selatan is in the medium category with a percentage of 59%.